2014
DOI: 10.1063/1.4870598
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of OH (X2Σ) in immediate vicinity of dielectric surface under pulsed dielectric barrier discharge at atmospheric pressure using two geometries of laser-induced fluorescence

Abstract: The behavior of the ground state OH radical was studied in humid air using pulsed surface dielectric barrier discharge. The validity of OH measurement in immediate vicinity of the dielectric surface was discussed using two geometries of laser-induced fluorescence (LIF) measurement, and surface distribution and temporal profiles of OH were examined. A comparison of parallel- and perpendicular-LIF techniques for OH measurement revealed that OH was mostly produced in a region several tens of μm above the dielectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…[26,27,43] This may also be the case under plasma conditions which shows deactivation with time on stream;t he fact that after three cycles this band has decreased considerably,yet the catalyst is still active would suggest that this species is,i ndeed, being converted into al ess active form (Au d+ ). Under the plasma conditions,i ti sp ostulated that reactive oxygen species (ROS) [1,[44][45][46] formed through the activation of the water leads to oxidation of the gold. This reactive oxygen species, which may be OH, for example,g enerated in the gas phase plasma will also increase the hydrolysis of the gold-support interface and lead to the loss of the interfacial gold species, represented by the band at 2095 cm À1 .P reviously reported density functional theory (DFT) calculations have demonstrated that the decoration of the surface with hydroxy groups significantly weakens the metal-support interaction and ad ewetting of the gold nanoparticle.T his loss of the interfacial gold which is exacerbated by the sintering of the gold particles,l eads to ad eactivation of the catalyst.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[26,27,43] This may also be the case under plasma conditions which shows deactivation with time on stream;t he fact that after three cycles this band has decreased considerably,yet the catalyst is still active would suggest that this species is,i ndeed, being converted into al ess active form (Au d+ ). Under the plasma conditions,i ti sp ostulated that reactive oxygen species (ROS) [1,[44][45][46] formed through the activation of the water leads to oxidation of the gold. This reactive oxygen species, which may be OH, for example,g enerated in the gas phase plasma will also increase the hydrolysis of the gold-support interface and lead to the loss of the interfacial gold species, represented by the band at 2095 cm À1 .P reviously reported density functional theory (DFT) calculations have demonstrated that the decoration of the surface with hydroxy groups significantly weakens the metal-support interaction and ad ewetting of the gold nanoparticle.T his loss of the interfacial gold which is exacerbated by the sintering of the gold particles,l eads to ad eactivation of the catalyst.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[47] Water has been observed to be activated in the gas phase under plasma conditions to form, for instance,OHand H 2 O + species. [1,[44][45][46]48] Theformer is thought to be ak ey intermediate from the water dissociation on the surface of gold and the subsequent reaction to form COOH before releasing CO 2 .Prior formation of the OH before adsorption would reduce the effective barriers,u sing the method reported by Wang et al, [49] from 2.87 to 0.73 eV on Au(111) and from 2.44 to 0.99 eV on Au(100). Further-more,t he activation barriers for the dissociation of H 2 O x as af unction of the charge x over gold was calculated and was found to be negative for cationic water (Figure S17), suggesting that H 2 O + is not stable and will dissociate into OH and H spontaneously.T herefore,t he plasma activated low temperature WGS is likely to be due to the facile activation of H 2 O reducing the overall activation barrier.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…This may also be the case under plasma conditions which shows deactivation with time on stream; the fact that after three cycles this band has decreased considerably, yet the catalyst is still active would suggest that this species is, indeed, being converted into a less active form (Au δ+ ). Under the plasma conditions, it is postulated that reactive oxygen species (ROS) formed through the activation of the water leads to oxidation of the gold. This reactive oxygen species, which may be OH, for example, generated in the gas phase plasma will also increase the hydrolysis of the gold‐support interface and lead to the loss of the interfacial gold species, represented by the band at 2095 cm −1 .…”
Section: Figurementioning
confidence: 99%
“…It being a very reactive oxidizing specie, it is important in plasma medicine and plasma assisted combustion issues. Many papers have been recently published on OH quantitative detection by LIF: in a pulsed corona discharge [10,11,12,13,14], in a DBD [15], in a pulsed DBD [16,17,18], in a plasma-jet [19,20,21,22,23,24,25], in a pulsed discharge over a liquid surface [13], in a pin-to-pin single filament discharge [26,27,28], in nanosecond discharges for plasma assisted combustion [29,30]. Transitions used for OH LIF detection are those of the OH (X 2 Π − A 2 Σ + ) 3064Å system.…”
Section: Introductionmentioning
confidence: 99%